Species composition and distribution of fish larvae in Lianga Bay, Surigao del Sur - Acabado, Cristy S.
The species composition and distribution of ichthyoplankton in Lianga Bay, Surigao del Sur was investigated in JUne 2004. A total of 37 families were recorded from horizontal tows collected in 32 sampling stations. The most dominant larvae were Gobiidae and Pomacentridae, which comprised 20.4 percent and 16.0 percent of all larvae ampled, respectively. Overall larval density was 4.2 ind. 100 M-3 (n=32; sd=5.0), with highest concentrations in the inner portion of the bay particularly in the west and southwest portions. On the ohter hand, egg density (mean=0.9 eggs m-3; n=32; sd=0.9) showed highest concentration near the coastline but further from the central basal portion of the bay. Patches of high egg concentrations suggest that Lianga Bay may serve as spawning ground for some species.